Uma Convenção Americana sobre Direitos Humanos de muitas mentes: o consenso regional interamericano - Tedesco, Thomaz Fiterman (2024)
The main argument of this thesis argues that the Inter-American Court of Human Rights has started to use, in recent years, the regional consensus method when interpreting the American Convention on Human Rights. The adoption of this method of interpretation, which tends to be positive for the court's legitimacy in relation to the States under its jurisdiction, occurred without prior theoretical development within the scope of the Inter-American Human Rights System. The method, created in the European Human Rights System, consists of determining and considering the understanding of the States Parties to the European Convention on Human Rights on the subject put on trial by the European Court of Human Rights, with the extraction of legal consequences depending on the existence or not of a majority on the matter. The comparative research between the two Courts, with a description of their contexts and institutional trajectories, was carried out using the historical-comparative method to seek to understand how the same interpretative method was embedded in the European System and not in the Inter-American System. Having noted the impact of these foundational moments as an explanatory element, the European regional consensus method and its dogmatic structure were presented, with a review of specialized literature and examples of the regional Court's jurisprudence to define its concept, scope, gradation and mode of application in that jurisdiction. Afterwards, empirical-quantitative research was carried out, using keywords entered in the Inter-American Court of Human Rights' search engine, to determine whether the use of the method migrated to the Americas, confirming the hypothesis. A case study on the evolution of the hermeneutical treatment of economic, social and cultural rights in inter-American contentious jurisdiction demonstrated that the use of the regional consensus method was one of the elements that allowed the Inter-American Court's contentious jurisdiction to be unlocked in relation to article 26 of the American Convention. In conclusion, it was found that the InterAmerican Court began to use the method, albeit in an unsystematic way, and that this could mean the beginning of a more direct dialogue with the hitherto ignored audience of the States Parties, with legitimacy benefits for the Inter-American Human Rights System